Constraints on the Design and Implementation of Monetary Policy in Oil Economies : The Case of Venezuela. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
By definition, fiscal dominance impedes the effective implementation of any monetary strategy aimed at controlling inflation. Economies that exhibit oil dominance-a situation in which oil exports largely affect the main macroeconomic indicators-may also exhibit fiscal dominance. However, in this case, the standard indicators used to gauge the presence of fiscal dominance may fail to give the appropriate signals. The main purpose of this paper is twofold: i) to present a simple framework to analyze fiscal dominance in oil exporting countries and ii) to test the hypothesis of the presence of oil dominance/fiscal dominance (OD/FD) in the case of Venezuela. Using VAR and VEC models it is possible to conclude that there is relevant evidence supporting the validity of the OD/FD hypothesis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet